2011
DOI: 10.4081/reumatismo.2006.230
|View full text |Cite
|
Sign up to set email alerts
|

Dactilitis and oligoarthritis after BCG immunotherapy in a patient affected by bladder cancer

Abstract: The treatment of bladder cancer with Bacillus of Calmette-Guerin (BCG) immunotherapy can induce the appearance of a reactive disorder. The Authors describe a 55-year-old male patient with bladder cancer treated with endovesical instillation of BCG immunotherapy, followed after the fifth application by asymmetric oligoarthritis and dactilitis. The observed positivity of both HLA-B27 and HLA-B51 antigens reinforces the hypothesis of a reactive form, possibly through "molecular mimicry" mechanism. The discontinua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Therefore, we included a total of 201 articles comprising 271 cases of BCG infection after intravesical instillation published since 1975. 1 14 , 17 – 19 , 21 31 , 33 – 39 , 41 – 49 , 51 71 , 73 80 , 82 84 , 87 97 , 99 , 101 , 102 , 104 , 105 , 107 119 , 121 138 , 140 151 , 153 – 168 , 170 , 171 , 173 180 , 182 189 , 192 , 193 , 195 202 , 205 208 , 210 214 , 218 , 219 , 221 223 , 225 232 Of these, 170 were individually detailed cases, and 31 were summarized in reports containing 2–13 cases. All data shown here were extracted from these case reports and case series, but occasionally articles lacked relevant clinical or microbiologic data.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we included a total of 201 articles comprising 271 cases of BCG infection after intravesical instillation published since 1975. 1 14 , 17 – 19 , 21 31 , 33 – 39 , 41 – 49 , 51 71 , 73 80 , 82 84 , 87 97 , 99 , 101 , 102 , 104 , 105 , 107 119 , 121 138 , 140 151 , 153 – 168 , 170 , 171 , 173 180 , 182 189 , 192 , 193 , 195 202 , 205 208 , 210 214 , 218 , 219 , 221 223 , 225 232 Of these, 170 were individually detailed cases, and 31 were summarized in reports containing 2–13 cases. All data shown here were extracted from these case reports and case series, but occasionally articles lacked relevant clinical or microbiologic data.…”
Section: Methodsmentioning
confidence: 99%
“…The most commonly involved joints are the knee, wrist, and ankle. In addition to arthritis, patients may exhibit dactylitis, urethritis, and uveitis (7,12,13,14). Elevated acute phase reactants, inflammatory response in the synovial fluid, and negative mycobacterial cultures of synovial fluid are expected findings of laboratory studies.…”
Section: Discussionmentioning
confidence: 99%
“…Poncet’s arthritis secondary to BCG usually occurs in men between 50 and 60 years of age, manifesting as asymmetric arthritis, normally found in wrists, ankles and knees, and fever associated in more than half of cases [ 19 ]. Dactylitis [ 20 ] and urethritis [ 21 ] have also been described as part of this clinical picture. It develops mostly after the fourth or fifth instillation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the mechanism by which the instillation of BCG induces Poncet’s disease is molecular mimicry, once the heat shock protein HSP65 of mycobacteria shares homology with a human cartilage proteoglycan, and also presents cross-reactivity with the haplotypes of HLA-DR1, DR3 and DR4, stimulating the secretion of cytokines and activation of CD8 (+) [ 20 ]. The autoimmune response induced by the administration of BCG occurs more frequently in patients with HLA-B27 (+) (nearly 60% of reported cases) or B7 (+) (which shows strong affinity with HLA-B27) [ 1 ].…”
Section: Discussionmentioning
confidence: 99%